Pengaruh Keberagaman Gender dan Pengungkapan Risiko Terhadap Efisiensi Investasi - Jaka Darmawan; Haris Roba’in (Penerbit Goodwood, 2022)
Purpose: This study aims to empirically examine the effect of gender diversity and risk disclosure on investment. Research Methodology: The population in this study are companies listed on the Jakarta Islamic Index 70 (JII 70) during the 2018-2020 research period which has a population of 41 companies using annual financial reports and annual reports in a row for 3 years so that the sample used is 123 sample data. This research was conducted using descriptive statistics and multiple linear regression with a 95% confidence level with secondary data collection methods and purposive sampling using the SPSS version 25 measurement program. Result: The test results and discussion prove that the independent variable Risk Disclosure has an influence on investment efficiency. The independent variable Gender Diversity has no effect on Investment Efficiency. Limitation: The limitations of the study were that there were only 2 X variables and only examined companies listed in JII 70. Contribution: Provides the benefit of knowledge about how the influence of gender diversity and risk disclosure can affect investment efficiency.